Executive functions in major depressive disorder - K. Dhawan; C.Y. Sudarshan; S. Begum (Sri Lanka Journal of Psychiatry, 2018)
Background It is reported that executive functions are impaired in a variety of neuropsychiatric syndromes, including depressive disorders. Studies on executive functions in depressive disorders are inconclusive.   Methods A total of 50 drug naïve patients with major depressive disorder were included in the study. The severity of depression was measured using the Hamilton Depression Rating Scale (HAM-D), and executive functions were assessed using the Digit Symbol Substitution Test, Digit Vigilance Test, Controlled Oral Word Association Test, Animal naming test, Verbal N back (1&2) test, Trail making test A & B and Stroop test as per the NIMHANS Neuropsychology Battery 2004 manual.   Results The mean age of the sample was 31.9 years. Females constituted 60% of the sample. A majority were Hindus, nearly 75% were from semi-urban areas, 66% were married, and 58% had a college education. Depression was associated with poor performance on executive functions except for working memory and set shifting. Older age, greater severity of depression, a longer duration of illness and the duration of the present episode were associated with poor performance on executive functions. A higher level of education was associated with better performance on executive functions.   Conclusions This cross-sectional assessment suggests that some aspects of executive functions are impaired in patients with major depressive disorder. Further studies in remitted patients, controlled for age, and education level are suggested.